Stability Study of Sunscreens with Free and Encapsulated UV Filters Contained in Plastic Packaging - Benedetta Briasco; Priscilla Capra; Barbara Mannucci; Paola Perugini (MDPI AG, 2017)
Sunscreens play a fundamental role in skin cancer prevention and in protection against photo-aging. UV filters are often photo-unstable, especially in relation to their vehicles and, being lipophilic substances, they are able to interact with plastic packaging. Finally, UV filter stability can be significantly affected by the routine use of the product at high temperatures. This work aims to study the stability of sunscreen formulations in polyethylene packaging. Butyl methoxydibenzoylmethane and octocrylene, both in a free form and as encapsulated filters were chosen as UV filters. Stability evaluations were performed both in the packaging and on the formulations. Moreover, a further two non-destructive techniques, near-infrared (NIR) spectroscopy and a multiple light scattering technique, were also used to evaluate the stability of the formulation. Results demonstrated clearly that all of the pack underwent significant changes in its elastic/plastic behavior and in external color after solar irradiation. From the evaluation of the extractable profile of untreated and treated packaging material an absorption of 2-phenoxyethanol and octocrylene were shown. In conclusion, the results highlighted clearly that a reduction of the UV filter in the formulation packed in high-density polyethylene/low-density polyethylene (HDPE/LDPE) material can occur over time, reducing the protective effect of the product when applied to the skin.